Firing clamp: a novel method for single-trial estimation of excitatory and inhibitory synaptic neuronal conductances - Chizhov, Anton; Malinina, Evgenya; Druzin, Michael; Graham, Lyle J.; Johansson, Staffan (Frontiers in Cellular Neuroscience, 2014)
Understanding non-stationary neuronal activity as seen in vivo requires estimation of both excitatory and inhibitory synaptic conductances from a single trial of recording. We propose a new intracellular recording method for this purpose called “firing clamp”. Synaptic conductances are estimated from the characteristics of artificially evoked probe spikes, namely the spike amplitude and the mean subthreshold potential, which are sensitive to both excitatory and inhibitory synaptic input signals. The probe spikes, timed at a fixed rate, are evoked in the dynamic-clamp mode by injected meander-like current steps, with the step duration depending on neuronal membrane voltage. We test the method with perforated-patch recordings from isolated cells stimulated by external application or synaptic release of transmitter, and validate the method with simulations of a biophysically-detailed neuron model. The results are compared with the conductance estimates based on conventional current-clamp recordings.